Measurement of the CP properties of Higgs boson interactions with 𝜏-leptons with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (The European physical journal. C, Particles and fields, 2023)
A study of the charge conjugation and parity (CP) properties of the interaction between the Higgs boson and tau-leptons is presented. The study is based on a measurement of CP-sensitive angular observables defined by the visible decay products of tau-leptons produced in Higgs boson decays. The analysis uses 139 fb-1 of proton-proton collision data recorded at a centre-of-mass energy of √s = 13 TeV with the ATLAS detector at the Large Hadron Collider. Contributions from CP-violating interactions between the Higgs boson and tau-leptons are described by a single mixing angle parameter phi tau in the generalised Yukawa interaction. Without constraining the H → tau tau signal strength to its expected value under the Standard Model hypothesis, the mixing angle phi tau is measured to be 9° +- 16°, with an expected value of 0° +- 28° at the 68% confidence level. The pure CP-odd hypothesis is disfavoured at a level of 3.4 standard deviations. The results are compatible with the predictions for the Higgs boson in the Standard Model.